La hipoterapia y su relación con la motricidad gruesa de los niños de 0 a 6 años con parálisis cerebral infantil del centro “Angelitos de Luz” período 2011 - Cuenca Capa, Jorge Luis (2012)
The delivery hippotherapy for children with Cerebral Palsy (PCI), according to their age and condition, the possibility of developing neurological maturation sequence, encouraging basic motor responses, this paper aims to understand how the "Hippotherapy is related to the Gross Motor of children aged 0 to 6 years old with Cerebral Palsy children's Center "Angelitos de Luz" 2011 period ". The overall objective was: To determine the influence of hippotherapy on gross motor skills of children with CP. This study is descriptive, quantitative and qualitative techniques were used as observation, interviews, surveys and scientific methods, descriptive, qualitative, statistical, analytical, synthetic and the instrument was hippotherapy test of gross motor function. The research population was 120 people, children (as), therapists and parents of the Centre "Angelitos de Luz", the sample was obtained by stratification where a total of 28 subjects. Instruments applied and the results obtained where it became clear that the children with CP, gross motor skills have improved posture, balance, increased muscle tone, coordination of arms and hands and walk with assistance. It concludes that Hippotherapy provides a means for facilitating and effective rehabilitation of children with CP, improving posture, balance and psychomotor skills and is recommended to design a specific program based on medical records seriously, as the test function gross motor for an extended period to take control of the child's development (a) and thus may come to have better living conditions and inclusion.